The effect of fantasy movie in writing for junior high school student - Dhita Wahyu Agustin; Erlik Widiyani Styati; Vita Vendityaningtyas (English Teaching Journal : A Journal of English Literature, Language and Education, 2022)
Fantasy movies are a type of movie that combines the imaginative and fantastic themes. Fantasy is something that does not really exist and only exists in the mind or mind. This research aims at investigating the effect of fantasy movie in writing for junior high school student. The quasi-experimental research used in this study. The participants were the students of SMPN 13 Madiun. The researchers used writing test to collect the data. In analyzing the data, the researchers use independent t-test. The result shows that there is a significant difference in students' narrative text writing skills between the experimental class and the control class. Students who are taught using fantasy movies gain higher scored than students who are taught using conventional teaching. The results obtained that the significance value of equal variances is assumed to be 0.000, it could be concluded that it is smaller than 0.05 (0.000 < 0.05). This means that fantasy movie media brings many benefits for students to write their writing skills